2015
DOI: 10.7324/japs.2015.50312
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC finger printing profile and evaluation of in vitro antidiabetic potential of medicinally important plant Cassia obtusa L. (Caesalpiniaceae)

Abstract: The aim of the study was to establish the finger printing profile and evaluation of in vitro antidiabetic potential of C. obtusa. In vitro antidiabetic activity was carried out according to the method adopted by Miller, 1959. HPTLC studies were carried out using CAMAG HPTLC system equipped with Linomat 5 applicator, TLC scanner 3 and Win cats-4 software for the active fractionation of aqueous-methanolic leaf extracts of C. obtusa. Among the various plant parts analyzed, leaf exhibited efficient inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus is a complex of metabolic diseases characterized by hyperglycemia caused by problems in insulin secretion, insulin dysfunction or both (Thenmozhi et al, 2015). The search for safer and more effective anti-diabetic agents without any side effects has been of interest to research.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a complex of metabolic diseases characterized by hyperglycemia caused by problems in insulin secretion, insulin dysfunction or both (Thenmozhi et al, 2015). The search for safer and more effective anti-diabetic agents without any side effects has been of interest to research.…”
Section: Introductionmentioning
confidence: 99%
“…The HPTLC method is simple, rapid, accurate, reproducible, selective and economic, can be used for quality control analysis and quantitative determination of the plant material. The qualitative determination of HPTLC profiles from medicinal plants is a fast expanding field of research to identify the chemical profiles with curative properties 28 . HPTLC studies have shown that it is more resourceful than ordinary TLC methods, as the spots are well resolved.…”
Section: Resultsmentioning
confidence: 99%
“…Plants are provided with secondary metabolites such as alkaloids, flavonoids, tannins, phenols and saponins which are also known as bioactive compounds and these bioactive compounds possess different biological activities which include antibacterial, antioxidant, anti-inflammatory, anticancer and antidiabetic and especially flavonoids already reported to treat type 2 diabetes [57][58][59][60] . In the recent years medicinal plants and their products have been investigated for potential benefits in the management of type 2 diabetes 61,62 .…”
Section: Resultsmentioning
confidence: 99%